ISLAM DAN PENDIDIKAN DI INDONESIA PASCA KEMERDEKAAN: ANALISIS TERHADAP SISTEM DAN KURIKULUM - Annisa Fitri; Khoirrun Yuridillah Isnaini; Nabil Ananda; Siti Hafiza; Rosila Antika; Yunita Sakila; Sirojul Fuadi (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to analyze the development of Islamic education in Indonesia after independence, focusing on the system and curriculum. The background of this study is based on the importance of Islamic education as an integral part of the national education system that helps shape the character and spiritual values of students. The main problem in this study is how the Islamic education system and curriculum developed in Indonesia after independence and what implications national education policy has for the substance and teaching methods of Islamic education at various levels of formal education. The purpose of the study is to determine the direction of policy, curriculum dynamics, and the contribution of Islamic educational institutions to the national education system. This study uses a literature review method with a descriptive qualitative approach. The results show that Islamic education has experienced significant development since independence, starting from formal recognition in the national education system to curriculum refinement that integrates Islamic and general sciences. The 2013 Curriculum and the Merdeka Curriculum are important milestones in strengthening Islamic education relevant to the needs of the 21st century. Suggestions put forward include the importance of strengthening teacher capacity, curriculum innovation based on Islamic values and local wisdom, and the development of integrated learning models that encourage collaboration between the spiritual and intellectual aspects of students.